MASALAH KEBUTUHAN SEKSUAL PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HAEMODIALISA - Haryani, Sri (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Sexual problems are most important problem in CRF patients undergoinghemodialysis. Feelings of shame and guilt for having sexual problems can cause a fearthat the problem will recur and eventually make a person avoid a sexual situation.Haemodialisa interview results in patients admitted in hospitals Curup decreased in termsof sexuality, quickly tired during intercourse, fatigue, and less passionate. This studyaimed to obtain sexual needs of patients with chronic renal failure undergoingHaemodialisa. This study uses qualitative research with phenomenological approach. Theresult showed that most informants are still sexual activity, four informants told declineand experiencing problems while two informants have no problems and all the informantscomplain quickly limp, tired and lackluster while undergoing sexual activity. 5 informantssaid there are problems since suffering a disease with chronic renal failure and oneinformant said that because of the age factor. This study is recommended to do healtheducation to couples, families and communities to always provide support to patients inorder to live life with optimism.